Caracterização imunológica de antígenos de Strongyloides stercoralis - Sudré, Adriana Pittella (2006)
The strongyloidiasis is caused by the intestinal nematode Strongyloides stercoralis, being prevalent in 3-13% infected patients in Brazil, and it typically occurs in the asymptomatic form. However, this nematode is considered of great importance for developing hyperinfection and dissemination in immunosupressed patients especially under corticoid therapy. The definitive diagnosis is normally done by detection of larvae on fecal samples; however, as the parasite load is often low in most cases and the larvae shedding is reduced and irregular, the diagnosis becomes extremely difficult. Thus, developing reliable serological methods for the diagnosis of strongyloidiasis becomes imperative. The objective of this study was to immunologically characterize epitopes of S. stercoralis larvae by analysis of its reactivity to serum samples of individuals with and without the disease. The search for S. stercoralis larvae on fecal samples by using the Rugai and Coprotest techniques was done with two objectives: to compare the sensibility of the two techniques, define the individuals positive and negative for strongyloidiasis, and to obtain filarioid larvae for the making of somatic antigen. The Western-blot technique was applied for the immunologic characterization of 101 serum samples that were divided into 6 groups: (G1) patients only positive for S. stercoralis by fecal exam, (G2) adults negative for any parasites by fecal exam (N=10), (G3) serum from umbilical cord (N=10), (G4) patients negative for any parasites by fecal exam from an area with high prevalence of strongyloidiasis (N=10), (G5) individuals with other helminth infection (N= 44), and (G6) individuals treated for strongyloidiasis (N=4). The results showed that strongyloidiasis was more prevalent in the Encanto community (6,4%) when compared to the Soledade community (2,7%). Additionally, a considerable fluctuation of larvae shedding was observed in these patients. In all the studied serum groups different reactivity profiles were observed, and the recognition of proteins with molecular mass varied from 6 to 129kDa. A protein band of approximately 26kDa presented a high frequency of reactivity (18/23) on the G1. The same band was also found in one serum from G3, 6 serum samples from G5 [hookworms (2/10), Ascaris lumbricoides (3/10) and Taenia sp. (2/10)] and one serum sample from G6. Two other reactive bands, one of approximately 33kDa and a duplet of approximately 21kDa, also have high frequency, 17/23 and 9/23, respectively. However, these two bands were also observed in all the other studied serum groups. Thus, we can suggest that the 26kDa band could be an important tool for the development of a diagnostic technique for strongyloidiasis